Efektifitas Pemberian Ekstrak Terong Belanda (Solanum betaceum) Terhadap Peningkatan Berat Testis Mencit (Mus musculus) yang Dipapar Timbal Asetat - Nurul Jannatul Wahidah; Reny I'tishom; Siti Khaerunnisa (FORIKES, 2020)
Male infertility with unknown definite etiology can be associated with lead exposure. Lead that accumulates in the body can cause oxidative stress and spermatogenesis disruption. To minimize the impact of lead exposure, it is necessary to use conventional methods with natural materials. One of them is the use of Solanum betaceum which have been proven to have secondary metabolic components that are antioxidants. This study aims to prove the effect of Dutch Eggplant (Solanum betaceum) extract to testicular weight of mice (Mus musculus) exposed to lead. This research was an true experimental research using male Mus musculus. Mice were 40 and divided into five groups randomly. Each group was consist of 8 mices. 1st group was negative control (K0), 2nd group was positive control (K1), 3rd group was exposed to lead + Solanum betaceum extract 100mg / KgBB (P1), 4th group was exposed to lead + Solanum betaceum extract 200mg / KgBB (P2), 5th group was exposed to lead + Solanum betaceum extract 400mg / KgBB (P3) for 35 days. Data were analyzed with One Way Anova and continued with T-Test. The results of this study prove that Dutch Eggplant (Solanum betaceum) extract significantly increase the testicular weight in mice exposed by lead acetate (p